DETERMINAN PEMBIAYAAN MURABAHAH (Studi Pada Bank Pembiayaan Rakyat Syariah Periode 2012-2017) - Syawal Harianto; Mizan Mizan; Haris Al Amin; Dwi Meilvinasvita (Ekonis: Jurnal Ekonomi dan Bisnis, 2019)
Abstract: This article was created to examine the determinants of murabahah financing as seen from the indicators: (a) Number of Sharia Rural Banks; (b) Third Party Funds; (c) Non Performing Financing. The data used is secondary data obtained from Sharia Banking publications by the Financial Services Authority and Bank Indonesia in the 2012-2017 period. This research approach method in two ways, namely associative and quantitative analysis. For the purpose of data analysis used multiple linear regression analysis and uses a hypothesis test that is Fisher test and student test. The test results show that simultaneously the number of sharia people's finance bank offices, third party funds and non-performing financing have a significant effect on murabahah financing and partially the number of sharia people's financing bank offices, third party funds and non-performing financing have a positive and significant impact on murabahah financing. This study recommends the Sharia People's Financing Bank (BPRS) to continuously monitor the number of sharia people's finance bank offices, third party funds and non-performing financing so that murabahah financing is able to deal with the monetary crisis Keywords: Murabahah Financing, Determinan,F isher Test, Studet Test